Pengenalan Digital Marketing Untuk Meningkatkan Kapasitas UMKM Di Dukuh Pedak - Sabania, Kania Irfa; Setiawan, Doni Agus; Ghanny, Rama; Khadapi, Muhammad Muamar; Wicaksono, Ahda Sabila; Saputra, Wijaya Whilly Hanggo; Pranoto, Bambang; Tariska, Rara Reza; Maharani, Widya Putri; Aprilia, Cahya; Muallidin, Isnaini (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
This article presents the results of the Community Service Program with the theme "Introduction to Digital Marketing to Enhance the Capacity of UMKM in Dukuh Pedak." This program aims to introduce digital marketing through TikTok to improve the capacity of UMKM in Dukuh Pedak. The method of this program was socialization, training, mentoring, and evaluation. The results showed that most participants began to understand the importance of digital marketing, and their commitment to the program was demonstrated through the completion of the provided Google Form. However, there was a decline in participant numbers in the second session due to scheduling conflicts with village activities, leading many target UMKM to be unavailable. The evaluation was conducted constructively, and the program concluded with the distribution of TikTok guidebooks and certificates. To ensure continued support, a WhatsApp group was created to facilitate ongoing consultation on digital marketing. Overall, utilizing TikTok as a digital marketing platform has had a positive impact on UMKM in Dukuh Pedak